Positive electrode active material for secondary battery and method for manufacturing the same
By controlling boron content in the mixture and using a specific manufacturing process, the method achieves a positive electrode active material with high specific surface area and reduced viscosity, addressing the productivity challenge in secondary battery production.
Patent Information
- Application Number
- JP2024118607
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-27
- Filing Date
- 2024-07-24
- Publication Date
- 2025-02-06
AI Technical Summary
The production of positive electrode active materials with high specific surface area for secondary batteries leads to reduced productivity, as existing methods do not effectively balance surface area enhancement with manufacturing efficiency.
A method involving the preparation of a mixture containing a lithium source, phosphate source, iron source, carbon source, and boron source, followed by granulation and heat treatment to produce a lithium transition metal compound with an olivine structure, where the boron content is controlled to maintain a specific surface area while reducing viscosity and improving productivity.
The method results in a positive electrode active material with enhanced specific surface area and reduced paste viscosity, leading to improved output characteristics and high productivity without compromising manufacturing efficiency.
Smart Images

Figure 2025019008000001 
Figure 2025019008000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a positive electrode active material for a secondary battery and a method for producing the same. [Background technology]
[0002] Lithium transition metal compounds having an olivine structure are known as positive electrode active materials that can be used in lithium ion secondary batteries. For example, Patent Document 1 proposes a boron-doped lithium insertion compound having an olivine structure. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Special Publication No. 2007-502249 Summary of the Invention [Problem to be solved by the invention]
[0004] Increasing the specific surface area of a positive electrode active material is considered as a method for obtaining high output characteristics in a secondary battery. However, when a positive electrode is manufactured using a positive electrode active material with a large specific surface area, the productivity may decrease. An object of one aspect of the present disclosure is to provide a positive electrode active material for a secondary battery and a manufacturing method thereof that reduce the decrease in productivity during the manufacture of a positive electrode. [Means for solving the problem]
[0005] The first aspect is a method for producing a positive electrode active material for a secondary battery, the method including: preparing a mixture containing a lithium source, a phosphate source, an iron source, a carbon source, a boron source containing an oxoacid of boron, and a liquid medium, granulating the mixture to obtain a precursor, and heat-treating the precursor to obtain a lithium transition metal compound having an olivine structure. In the mixture, the total molar amount of boron atoms contained in the boron source is greater than 0 mol % and less than 3 mol % relative to the total molar amount of iron atoms contained in the iron source.
[0006] The second aspect includes a lithium transition metal compound having an olivine structure, the composition having a boron content greater than 0 ppm and less than 1900 ppm, and a specific surface area of 15 m 2 / g or more. Effect of the Invention
[0007] According to one aspect of the present disclosure, it is possible to provide a positive electrode active material for a secondary battery, which reduces a decrease in productivity during the production of a positive electrode, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] In this specification, the term "step" includes not only an independent step, but also a step that cannot be clearly distinguished from other steps, as long as the intended purpose of the step is achieved. In addition, the content of each component in the composition means the total amount of the multiple substances present in the composition, unless otherwise specified, when multiple substances corresponding to each component are present in the composition. Furthermore, the upper and lower limits of the numerical ranges described in this specification can be arbitrarily selected and combined from the numerical values exemplified as the numerical ranges. Hereinafter, the embodiments of the present invention will be described in detail. However, the embodiments shown below are examples of secondary battery positive electrode active materials and their manufacturing methods for embodying the technical ideas of the present invention, and the present invention is not limited to the secondary battery positive electrode active materials and their manufacturing methods shown below.
[0009] Method for producing positive electrode active material for secondary battery The method for producing a positive electrode active material for a secondary battery includes a preparation step of preparing a mixture containing a lithium source, a phosphate source, an iron source, a carbon source, a boron source containing an oxoacid of boron, and a liquid medium, a granulation step of granulating the prepared mixture to obtain a precursor, and a heat treatment step of heat treating the prepared precursor to obtain a lithium transition metal compound having an olivine structure.
[0010] The lithium transition metal compound obtained by heat-treating the mixture obtained by the primary addition of the boron source has a sufficient specific surface area, while being capable of reducing the viscosity of the positive electrode material paste used in the manufacture of a positive electrode for a secondary battery. The low viscosity of the positive electrode material paste allows for the efficient manufacture of a positive electrode having good output characteristics. The primary addition of the boron source means that the boron source is added to a raw material mixture of a lithium transition metal compound having an olivine structure, and the lithium transition metal compound is synthesized in the presence of the boron source. The case where the boron source is added to the synthesized lithium transition metal compound and heat treatment or the like is performed is referred to as the secondary addition.
[0011] In the preparation step, a mixture containing a lithium source, a phosphate source, and an iron source constituting a lithium transition metal compound, as well as a carbon source, a boron source, and a liquid medium is prepared. The mixture can be prepared by mixing the lithium source, the phosphate source, the iron source, the carbon source, the boron source, and the liquid medium. The mixing method may be appropriately selected from commonly used mixing methods. The mixture may be a pulverized product containing the lithium source, the phosphate source, the iron source, the carbon source, the boron source, and the liquid medium, or may be a slurry having fluidity.
[0012] The lithium source constituting the mixture may contain a lithium compound. Examples of the lithium compound include lithium phosphate, lithium carbonate, and lithium hydroxide. The lithium source may preferably contain at least lithium phosphate (e.g., Li3PO4). The content of the lithium source contained in the mixture may be, for example, a ratio of the number of moles of lithium contained in the lithium source to the total number of moles of phosphorus contained in the mixture, which may be greater than 0.9 and less than 1.1, and preferably 0.95 or more and 1.05 or less. The content of the lithium source contained in the mixture may be, for example, a ratio of the number of moles of lithium contained in the lithium source to the number of moles of iron atoms contained in the iron source, which may be 1 or more and 1.1 or less. It may be preferably 1.01 or more, or 1.02 or more, and preferably 1.07 or less, or 1.05 or less.
[0013] The iron source constituting the mixture may include an iron compound, iron alone, etc. Examples of the iron compound include phosphates, nitrates, carbonates, oxides, etc., and may include at least phosphates (e.g., Fe3(PO4)2). When the iron contained in the iron compound is divalent iron, the carbonization of the carbon source tends to occur before the crystal growth of the lithium transition metal compound, which tends to increase the specific surface area of the obtained positive electrode material and increase the discharge capacity under high load conditions. The content of the iron source contained in the mixture may be, for example, more than 0.8 and 1.8 or less, preferably 0.9 or more and 1.6 or less, as the ratio of the number of moles of iron atoms to the total number of moles of phosphorus contained in the mixture.
[0014] The phosphate source constituting the mixture may include a phosphate compound. Examples of the phosphate compound include a phosphate compound containing lithium, a phosphate compound containing iron, and a phosphate compound not containing lithium and iron. Examples of the phosphate compound containing lithium include lithium phosphate, and may also serve as the lithium source in the mixture. Examples of the phosphate compound containing iron include iron phosphate, and may also serve as the iron source in the mixture. Examples of the phosphate compound not containing lithium and iron include ammonium phosphate and phosphoric acid. In addition, ammonium dihydrogen phosphate may be used as the ammonium phosphate. The content of the phosphate compound not containing lithium and iron contained in the mixture may be, for example, more than 0 mol% and 3 mol% or less as a ratio of the number of moles to the total molar amount of iron atoms contained in the mixture, and may be preferably 0.5 mol% or more and 2.5 mol% or less, 1 mol% or more and 2 mol% or less, or 1.5 mol% or more and 1.8 mol% or less. When the phosphate compound not containing lithium and iron contained in the mixture is within the above range, a positive electrode material with improved crystallinity tends to be obtained.
[0015] The carbon source constituting the mixture may be carbon alone or a carbon compound capable of generating carbon by heat treatment. Examples of carbon compounds contained in the carbon source include dextrin, sucrose, starch, etc., and may contain at least one selected from the group consisting of these. From the viewpoint of the carbonization rate, it is preferable that the carbon source contains dextrin. The content of the carbon source contained in the mixture may be, for example, 15% by mass or more and 30% by mass or less, preferably 16% by mass or more, 17% by mass or more, or 18% by mass or more, and preferably 25% by mass or less, or 20% by mass or less, based on the total mass of iron atoms contained in the mixture.
[0016] The boron source constituting the mixture may contain an oxoacid of boron. The boron source may contain a boron oxide capable of generating an oxoacid of boron, and may be an oxygen-containing boron compound that does not contain a metal element or phosphorus. Examples of the boron source include orthoboric acid (H3BO3), metaboric acid (HBO2), and the like. nExamples of the boron source include oxygen-containing boron compounds such as boron oxoacids such as boron trioxide (BO), boron dioxide (BO), tetraboron trioxide (BO), and tetraboron pentoxide (BO). The boron source may contain at least a boron oxoacid, and may contain at least orthoboric acid. The total molar amount of boron atoms contained in the boron source contained in the mixture may be, for example, more than 0 mol% and less than 3 mol% with respect to the total molar amount of iron atoms contained in the mixture, and may be preferably 0.1 mol% to 2.5 mol%, 0.2 mol% to 1.8 mol%, 0.4 mol% to 1.6 mol%, or 0.5 mol% to 1.5 mol%. In one embodiment, the total molar amount of boron atoms relative to the total molar amount of iron atoms in the mixture may be 0.1 mol% or more, 0.3 mol% or more, 0.5 mol% or more, 0.6 mol% or more, 0.8 mol% or more, 0.9 mol% or more, 1.0 mol% or more, or 1.4 mol% or more, and may be 2.2 mol% or less, 1.8 mol% or less, 1.6 mol% or less, 1.4 mol% or less, 1.2 mol% or less, or 0.8 mol% or less. By having the content of the boron source contained in the mixture within the above range, it tends to be easier to maintain the rate characteristics and improve the paste viscosity at the same time.
[0017] The liquid medium may contain at least water, and may further contain a water-soluble organic solvent such as alcohol or acetone in addition to water. The mixture may be configured as a slurry having fluidity. The content of the iron source contained in the mixture may be, for example, 3% by mass or more and 15% by mass or less, preferably 4% by mass or more and 10% by mass or less, in terms of the content of iron atoms.
[0018] The mixture may further include a first metal source containing a first metal element including at least one selected from the group consisting of manganese (Mn), cobalt (Co), nickel (Ni) and copper (Cu) as necessary. The first metal source may further include a metal compound containing the first metal element, a simple substance of the first metal element, etc. Examples of the metal compound include phosphates, nitrates, carbonates, oxides, etc., and may include at least phosphate. The content of the first metal source contained in the mixture may be 0 or more and less than 1, for example, as the ratio of the number of moles of the first metal element to the total number of moles of iron and the first metal element contained in the mixture, and may be preferably 0.8 or less, 0.7 or less, 0.4 or less, or 0.2 or less. The first metal atom may preferably include at least one selected from the group consisting of manganese (Mn), cobalt (Co) and nickel (Ni).
[0019] The mixture may further contain a second metal source containing a second metal element containing at least one selected from the group consisting of Group 2 elements, Group 3 elements, Group 4 elements, Group 6 elements, Group 12 elements, Group 13 elements, Group 14 elements, and lanthanoids, as necessary. The second metal source may contain a metal compound containing the second metal element, a simple substance of the second metal element, etc. Examples of the metal compound include phosphates, oxides, carbonates, halides, etc., and may contain at least phosphates.
[0020] The second metal element may preferably include at least one selected from the group consisting of magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), scandium (Sc), yttrium (Y), titanium (Ti), zirconium (Zr), chromium (Cr), molybdenum (Mo), zinc (Zn), aluminum (Al), gallium (Ga), indium (In), silicon (Si), germanium (Ge) and cerium (Ce). The second metal element may preferably include at least one selected from the group consisting of molybdenum (Mo), magnesium (Mg), titanium (Ti), zirconium (Zr), chromium (Cr), aluminum (Al) and cerium (Ce).
[0021] The content of the second metal source contained in the mixture, for example, as the ratio of the number of moles of second metal atoms to the total number of moles of phosphorus contained in the mixture, may be from 0 to less than 1, and preferably from 0 to 0.5, from 0 to 0.3, from 0 to 0.1, or from 0 to 0.03. Furthermore, the ratio of the total number of moles of iron atoms and second metal atoms to the total number of moles of phosphorus contained in the mixture may be greater than 0.9 and less than 1.1, and preferably from 0.95 to 1.05.
[0022] The mixture may contain a pH adjuster as necessary. Examples of pH adjusters include citric acid, sulfuric acid, ammonium carbonate, etc. The content of the pH adjuster in the mixture may be appropriately adjusted so that the mixture has a desired pH.
[0023] The mixture can be prepared by grinding a composition containing a lithium source, an iron source, a phosphate source, a liquid medium, etc. The mixture may be prepared, for example, by any of the following preparation methods (1) to (4).
[0024] (1) The first preparation method may include grinding a first pre-mixture containing a lithium source, a phosphate source, an iron source, and a liquid medium to obtain a first ground product, and mixing the first ground product with a carbon source and a boron source to obtain a mixture.
[0025] (2) The second preparation method may include grinding a second pre-mixture containing a lithium source, a phosphate source, an iron source, a carbon source, and a liquid medium to obtain a second ground product, and mixing the second ground product with a boron source to obtain a mixture.
[0026] (3) The third preparation method may include grinding a third pre-mixture containing a lithium source, a phosphate source, an iron source, a boron source, and a liquid medium to obtain a third ground product, and mixing the third ground product with a carbon source to obtain a mixture.
[0027] (4) A fourth preparation method may include grinding a fourth pre-mixture including a lithium source, a phosphate source, an iron source, a carbon source, a boron source, and a liquid medium to obtain a mixture as a fourth ground product.
[0028] The pulverization treatment can be carried out, for example, using a ball mill, a vibration mill, a roll mill, a mortar and pestle mill, etc. The pulverized product obtained by the pulverization treatment may be a slurry having fluidity. The pulverization treatment time may be, for example, 10 hours or more, preferably 20 hours or more, or 60 hours or less.
[0029] The pulverization may be carried out so that the volume average particle size of the pulverized product is 0.05 μm or more and 1 μm or less, preferably 0.1 μm or more and 0.5 μm or less. The solid content concentration of the pulverized product may be, for example, 5% by mass or more and 50% by mass or less, preferably 10% by mass or more and 30% by mass or less. The volume average particle size of the pulverized product is measured using a laser diffraction type particle size distribution measuring device.
[0030] The method for mixing the pulverized product with the carbon source or boron source may be appropriately selected from commonly used mixing methods. The method for mixing the pulverized product with the carbon source or boron source may include a pulverization treatment. The time for the pulverization treatment may be, for example, 1 minute or more and 60 hours or less.
[0031] The volume average particle size of the mixture prepared in the preparation step may be, for example, 0.05 μm to 1 μm, and preferably 0.1 μm to 0.5 μm. The solid content concentration of the mixture may be, for example, 5% by mass to 50% by mass, and preferably 10% by mass to 30% by mass.
[0032] In the granulation step, at least a portion of the liquid medium contained in the prepared mixture is removed to obtain a precursor as a granulated, dried product. 50may be, for example, 1 μm or more and 20 μm or less, preferably 5 μm or more, or 7 μm or more, and preferably 16 μm or less. Methods for drying the mixture include spray drying, fluidized bed drying, and the like, with spray drying being preferred. Here, the volume average particle size of the precursor is measured using a laser diffraction particle size distribution measuring device.
[0033] When the granulation step is carried out by spray drying, the specific conditions of the spray drying may be, for example, a ratio of the amount of gas supplied to the amount of mixture supplied, in terms of volume ratio, of 500 to 4000, preferably 800 to 2000. The drying temperature may be, for example, 100°C to 170°C, preferably 100°C to 120°C.
[0034] In the heat treatment step, the prepared precursor is heat-treated to obtain a heat-treated product containing a lithium transition metal compound having an olivine structure. The heat treatment temperature may be, for example, in the range of 500°C to 700°C, and preferably in the range of 600°C to 650°C. The heat treatment step may include raising the temperature to a predetermined heat treatment temperature, maintaining the heat treatment temperature, and lowering the temperature from the heat treatment temperature. The rate of temperature rise to the heat treatment temperature may be, for example, from room temperature, 2.5°C / min to 5°C / min, preferably 3.0°C / min or more, or 3.3°C / min or more, and preferably 4.5°C / min or less, or 4.2°C / min or less. The heat treatment time for maintaining the heat treatment temperature may be, for example, 0.1 hours to 15 hours, preferably 0.2 hours to 0.3 hours, or 0.4 hours, and preferably 12 hours or less, 8 hours or less, or 5 hours or less. The rate of temperature decrease from the heat treatment temperature to room temperature may be, for example, 1° C. / min or more and 600° C. / min or less.
[0035] The atmosphere in the heat treatment step may be an inert gas atmosphere containing a rare gas such as nitrogen or argon. The inert gas atmosphere may have an inert gas content of, for example, 90% by volume or more, preferably 95% by volume or more, or 98% by volume or more. The heat treatment may be performed under a flow of an inert gas.
[0036] The pressure in the atmosphere of the heat treatment step may be atmospheric pressure, or may be pressurized or reduced pressure. The pressurized condition may be, for example, greater than 0 MPa and less than 0.1 MPa, preferably greater than 0 MPa and less than 0.05 MPa, as gauge pressure. The reduced pressure condition may be, for example, greater than -0.1 MPa and less than 0 MPa, preferably greater than -0.05 MPa and less than 0 MPa, as gauge pressure.
[0037] The heat treatment of the precursor can be carried out, for example, using a box-type atmospheric furnace, a tubular furnace, a carbon rotary kiln, etc. The heat treatment of the precursor can be carried out, for example, by filling the precursor into a crucible, boat, etc. made of aluminum oxide. In addition to aluminum oxide materials, carbon materials such as graphite, boron nitride (BN), molybdenum materials, etc. can also be used.
[0038] The heat-treated product obtained in the heat treatment step may be subjected to treatments such as pulverization, dispersion, washing, filtration, classification, etc., and may be subjected to at least pulverization and classification.
[0039] Cathode active material for secondary batteries The positive electrode active material for a secondary battery (hereinafter also simply referred to as "positive electrode active material") contains a lithium transition metal compound having an olivine structure, and the composition of the positive electrode active material may have a boron content of more than 0 ppm and less than 1900 ppm. 2 The positive electrode active material may be one produced by the above-mentioned method for producing a positive electrode active material for a secondary battery.
[0040] The positive electrode active material contains boron in its composition, and the boron content in the composition is greater than 0 ppm and less than 1900 ppm, so that the viscosity of the positive electrode material paste containing the positive electrode active material can be reduced. This is thought to be because, for example, the presence of a boron compound between primary particles constituting the positive electrode active material made of secondary particles can reduce the absorption of a solvent such as NMP into the inside of the secondary particles of the positive electrode active material.
[0041] The viscosity of the positive electrode material paste containing the positive electrode active material is measured, for example, as follows. (1) Preparation of the paste for measurement A carbon material as a conductive additive, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a solvent are mixed in a mass ratio of 1:1:14.85 to prepare a carbon mixture. The carbon mixture and the positive electrode active material are mixed in a mass ratio of 1.00:1.08 with a stirrer for 5 minutes to obtain a first mixture. NMP is added so that the solid concentration becomes 45.5%, and the mixture is further mixed with a stirrer for 10 minutes to obtain a paste for measurement. (2) Paste viscosity measurement conditions The viscosity of the measurement paste is measured twice at 25° C. using an E-type viscometer, and the arithmetic mean value of the two measured values is regarded as the paste viscosity of the positive electrode material paste.
[0042] The carbon material used to prepare the measurement paste is CABOT LITX-200 (CABOT and LITX are registered trademarks). W#9700 (manufactured by Kureha Corporation) is used as the PVDF. The paste viscosity of the measurement paste may be, for example, 2000 mPa·s or less, and preferably 1700 mPa·s or less. The paste viscosity of the measurement paste may be 1400 mPa·s or more.
[0043] The positive electrode active material contains boron. The boron content of the positive electrode active material may be preferably 100 ppm or more, 200 ppm or more, 300 ppm or more, 400 ppm or more, 580 ppm or more, or 800 ppm or more, and may be preferably 1500 ppm or less, 1200 ppm or less, 1000 ppm or less, 800 ppm or less, 700 ppm or less, or 400 ppm or less. When the boron content is within the above range, the paste viscosity tends to be further reduced.
[0044] The positive electrode active material may include, for example, secondary particles formed by aggregating a plurality of primary particles having a carbon material attached to the surface. The boron contained in the positive electrode active material can be considered to be contained in, for example, the carbon material attached to the primary particles. That is, the positive electrode active material may include secondary particles formed by aggregating a plurality of primary particles having a carbon material containing boron attached to the surface. The primary particles may include a lithium transition metal compound having an olivine structure, and the primary particles may be substantially composed of a lithium transition metal compound having an olivine structure. Here, "substantially" means that components other than the lithium transition metal compound having an olivine structure that are inevitably contained in the primary particles are not excluded, and the content of components other than the lithium transition metal compound having an olivine structure in the primary particles is, for example, 1% by mass or less, preferably 0.5% by mass or less.
[0045] A carbon material may be attached to the surface of the primary particles constituting the positive electrode active material. The attachment of the carbon material may be, for example, physical adsorption due to van der Waals forces or the like. The attached carbon material may be in the form of particles or a film, and preferably in the form of a film. The amount of the carbon material attached to the primary particles can be evaluated as the carbon content contained in the positive electrode active material. The carbon content in the positive electrode active material may be, for example, greater than 0.5 mass% and not more than 1.8 mass%, and preferably not more than 1.6 mass%, not more than 1.5 mass%, or not more than 1.4 mass%, relative to the total mass of the positive electrode active material. The carbon content in the positive electrode active material may be, for example, 0.8 mass% or more, and preferably not less than 0.9 mass%, not less than 1.0 mass%, or not less than 1.1 mass%, relative to the total mass of the positive electrode active material. When the carbon content in the positive electrode active material is within the above range, there is a tendency that the load characteristics can be improved while maintaining a high pellet density. The carbon content in the positive electrode active material can be measured, for example, by a total organic carbon meter (TOC meter).
[0046] The lithium transition metal compound contained in the positive electrode active material may be a phosphate compound having an olivine structure and containing at least an iron atom, a lithium atom, and a phosphorus atom in its composition. The lithium transition metal compound may further contain a first metal atom containing at least one selected from the group consisting of manganese (Mn), cobalt (Co), nickel (Ni), copper (Cu), and the like, as necessary. The first metal atom may preferably contain at least one selected from the group consisting of manganese (Mn), cobalt (Co), and nickel (Ni). In addition, the lithium transition metal compound may further contain a second metal atom containing at least one selected from the group consisting of Group 2 elements, Group 3 elements, Group 4 elements, Group 6 elements, Group 12 elements, Group 13 elements, Group 14 elements, and lanthanoids, as necessary.
[0047] The second metal atom may preferably include at least one selected from the group consisting of magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), scandium (Sc), yttrium (Y), titanium (Ti), zirconium (Zr), chromium (Cr), molybdenum (Mo), zinc (Zn), aluminum (Al), gallium (Ga), indium (In), silicon (Si), germanium (Ge) and cerium (Ce). The second metal atom may preferably include at least one selected from the group consisting of molybdenum (Mo), magnesium (Mg), titanium (Ti), zirconium (Zr), chromium (Cr), aluminum (Al) and cerium (Ce).
[0048] The lithium transition metal compound may have the following composition, for example. The ratio of the number of moles of lithium atoms to the number of moles of phosphorus atoms may be greater than 0.9 and less than 1.1, preferably 0.95 to 1.05. The ratio of the number of moles of iron atoms to the number of moles of phosphorus atoms may be greater than 0.8 and less than 1, preferably 0.9 to 1. The ratio of the number of moles of the first metal atoms to the number of moles of phosphorus atoms may be greater than 0 and less than 1, and may be 0.8 or less, 0.7 or less, 0.4 or less, or 0.2 or less. Furthermore, the ratio of the total number of moles of iron atoms and the first metal atoms to the number of moles of phosphorus atoms may be greater than 0.9 and less than 1.1, preferably 0.95 to 1.05.
[0049] The ratio of the number of moles of the second metal atoms to the number of moles of phosphorus atoms may be 0 or more and less than 1, and preferably 0 or more and 0.5 or less, 0 or more and 0.3 or less, 0 or more and 0.1 or less, or 0 or more and 0.03 or less. Furthermore, the ratio of the total number of moles of iron atoms and the second metal atoms to the number of moles of phosphorus atoms may be more than 0.9 and less than 1.1, and preferably 0.95 or more and 1.05 or less.
[0050] The lithium transition metal compound may have a composition represented by the following formula (1), for example.
[0051] Lix (Fe (1-y) M 1 y ) (1-z) M 2 z (PO4) w (1)
[0052] In the formula, x, y, z, and w may satisfy 0.9 < x < 1.3, 0 ≤ y < 1, 0 ≤ z < 0.3, and 0.9 ≤ w ≤ 1.3. M 1 may contain at least one metal element selected from the group consisting of Mn, Co, and Ni. M 2 may contain at least one metal element selected from the group consisting of W, Mo, Mg, Zr, Ti, Al, Ce, and Cr.
[0053] x, y, z, and w may preferably satisfy at least one of 0.95 < x < 1.1, 0 ≤ y < 0.8, 0 ≤ y < 0.7, 0 ≤ y < 0.4, 0 ≤ y < 0.2, 0 ≤ z < 0.1, 0 ≤ z < 0.03, 0.95 ≤ w ≤ 1.1, 1.0 ≤ w ≤ 1.1, and 1.005 ≤ w ≤ 1.1.
[0054] The specific surface area of the positive electrode active material is preferably 14 m 2 / g or more, 17 m 2 / g or more, or 18 m 2 / g or more. The specific surface area may be, for example, 45 m 2 / g or less, 30 m 2 / g or less, 24 m 2 / g or less, or 20 m 2 / g or less. When the specific surface area is within the above range, the output characteristics (e.g., rate characteristics) in the secondary battery tend to be more improved. The specific surface area of the positive electrode active material may be the specific surface area measured by the BET method and is measured by the one-point method using nitrogen gas based on the BET (Brunauer Emmett Teller) theory.
[0055] The positive electrode active material may have an oil absorption of, for example, 40 ml / 100 g or less, or 30 ml / 100 g or less, preferably 29 ml / 100 g or less, or 28 ml / 100 g or less. The oil absorption of, for example, N-methyl-2-pyrrolidone may be 20 ml / 100 g or more, or 26 ml / 100 g. When the oil absorption of the positive electrode active material for N-methyl-2-pyrrolidone is within the above range, the secondary particles can be densified, and the pellet density tends to be improved. The oil absorption of the positive electrode material is measured according to the method specified in JIS K5101-13-1.
[0056] A positive electrode formed using the positive electrode active material has excellent packing properties in the positive electrode active material layer that constitutes the positive electrode. The packing properties of the positive electrode active material layer can be evaluated by the density of a pellet made of the positive electrode active material and formed under predetermined conditions. The positive electrode active material has a pellet density of, for example, 2.00 g / cm when compressed into a pellet at a pressure of 3.5 MPa. 3 or more, preferably 2.02 g / cm 3 More than 2.04g / cm 3 More than 2.05g / cm 3 More than 2.06g / cm 3 or more than 2.08g / cm 3 The pellet density may be, for example, 2.3 g / cm 3 or less than 2.2g / cm 3 It may be the following:
[0057] Volume average particle size D of the positive electrode active material 50 may be, for example, 1 μm or more and 20 μm or less, preferably 4 μm or more, 6 μm or more, 8 μm or more, or 9 μm or more. The volume average particle size may be preferably 18 μm or less, 15 μm or less, 12 μm or less, or 11 μm or less. The volume average particle size of the positive electrode active material is determined as a particle size corresponding to 50% of the volume cumulative from the small diameter side in the volume-based cumulative particle size distribution. The volume-based cumulative particle size distribution is measured, for example, by a laser diffraction type particle size distribution measuring device. When the volume average particle size of the positive electrode active material is within the above range, the workability during production tends to be improved.
[0058] Positive electrodes for secondary batteries The positive electrode for the secondary battery includes a current collector and a positive electrode active material layer disposed on the current collector and including the above-mentioned positive electrode active material. A secondary battery including such a positive electrode can achieve excellent charge / discharge capacity. The positive electrode for the secondary battery may be, for example, a positive electrode for a lithium ion secondary battery.
[0059] The density of the positive electrode active material layer is, for example, 1.6 g / cm 3 More than 2.8g / cm 3 or less, preferably 1.8 g / cm 3 More than 2.6g / cm 3 Below, 1.9g / cm 3 More than 2.5g / cm 3 Below 2.0g / cm 3 More than 2.4g / cm 3 or less than 2.05g / cm 3 More than 2.3g / cm 3 The density of the positive electrode active material layer is calculated by dividing the mass of the positive electrode active material layer by the volume of the positive electrode active material layer.
[0060] Examples of the material of the current collector include aluminum, nickel, stainless steel, etc. The positive electrode active material layer can be formed by mixing the above-mentioned positive electrode material, conductive assistant, binder, etc. together with a solvent to obtain an electrode composition, applying the composition onto the current collector, and then performing a drying process, a pressure process, etc. Examples of the conductive assistant include natural graphite, artificial graphite, acetylene black, etc. Examples of the binder include polyvinylidene fluoride, polytetrafluoroethylene, polyamide acrylic resin, etc. Examples of the solvent include N-methyl-2-pyrrolidone (NMP), etc.
[0061] secondary battery The secondary battery includes the above-mentioned positive electrode for secondary batteries. The secondary battery may be, for example, a lithium ion secondary battery. The lithium ion secondary battery includes, in addition to the positive electrode for secondary batteries, a negative electrode for lithium ion secondary batteries, a non-aqueous electrolyte, a separator, and the like. For the negative electrode, non-aqueous electrolyte, separator, and the like for lithium ion secondary batteries in the lithium ion secondary battery, those for lithium ion secondary batteries described in, for example, JP 2002-075367 A, JP 2011-146390 A, and JP 2006-12433 A (the entire disclosures of which are incorporated herein by reference) can be appropriately used.
[0062] The invention according to the present disclosure may include, for example, the following aspects. [1] Providing a mixture including a lithium source, a phosphate source, an iron source, a carbon source, a boron source including an oxoacid of boron, and a liquid medium; granulating the mixture to obtain a precursor; and heat treating the precursor to obtain a lithium transition metal compound having an olivine structure. the mixture has a total molar amount of boron atoms contained in the boron source that is greater than 0 mol % and less than 3 mol % relative to the total molar amount of iron atoms contained in the iron source.
[0063] [2] The mixture is prepared by grinding a premix containing a lithium source, a phosphate source, an iron source, and a liquid medium, and then mixing the premix with a carbon source and a boron source; or A premix containing a lithium source, a phosphate source, an iron source, a carbon source, and a liquid medium is ground, and then mixed with a boron source to prepare the premix. A premix containing a lithium source, a phosphate source, an iron source, a boron source and a liquid medium is milled, and then a carbon source is mixed therein; or The method for producing a positive electrode active material for a secondary battery according to [1], wherein the positive electrode active material is prepared by pulverizing a preliminary mixture containing a lithium source, a phosphate source, an iron source, a carbon source, a boron source, and a liquid medium.
[0064] [3] The method for producing a positive electrode active material for a secondary battery according to [2], wherein the pulverization treatment is carried out using a ball mill for 10 hours or more.
[0065] [4] The method for producing a positive electrode active material for a secondary battery according to any one of [1] to [3], wherein the mixture has a mass ratio of the carbon source to the iron atoms of 15 mass% or more and 30 mass% or less.
[0066] [5] The precursor has a volume average particle size D 50 The method for producing a positive electrode active material for a secondary battery according to any one of [1] to [4], wherein the average particle size is 1 μm or more and 20 μm or less.
[0067] [6] The method for producing a positive electrode active material for a secondary battery according to any one of [1] to [5], wherein the heat treatment is carried out in a nitrogen atmosphere at 500° C. or higher and 700° C. or lower.
[0068] [7] A lithium transition metal compound having an olivine structure, a boron content in the composition being greater than 0 ppm and less than 1900 ppm, and a specific surface area of 15 m 2 / g or more.
[0069] [8] The positive electrode active material for a secondary battery according to [7], which has an oil absorption of 30 ml / 100 g or less in N-methyl-2-pyrrolidone.
[0070] [9] When compressed into pellets at 3.5 MPa, the pellet density is 2.00 g / cm 3 The positive electrode active material for a secondary battery according to [7] or [8] above.
[0071]
[10] The positive electrode active material for a secondary battery according to any one of [7] to [9], wherein the lithium transition metal compound has a composition represented by the following formula:
[0072] Li x (Fe (1-y) M 1 y ) (1-z) M 2 z (PO4)w
[0073] In the formula, x, y, z, and w satisfy 0.9 < x < 1.3, 0 ≤ y < 1, 0 ≤ z < 0.3, and 0.9 ≤ w ≤ 1.3. M 1 contains at least one metal element selected from the group consisting of Mn, Co, and Ni. M 2 contains at least one metal element selected from the group consisting of Mo, Mg, Zr, Ti, Al, Ce, and Cr.
Examples
[0074] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples.
[0075] Example 1 Preparation step 1662.0 g of a slurry prepared by dispersing iron phosphate (Fe3(PO4)2) in pure water so that the concentration of iron atoms is 7.22% by mass, 86.3 g of lithium phosphate (Li3PO4), 4.2 g of ammonium dihydrogen phosphate, 0.74 g of orthoboric acid (H3BO3), 6.0 g of citric acid, and 1092 g of pure water were placed in a ball mill container and pulverized and mixed for 40 hours using zirconia balls to obtain a pulverized product. 149.6 g of a 15% by mass dextrin solution was added to the obtained pulverized product and pulverized for another 3 hours to obtain a mixture.
[0076] The ratio of the number of moles of lithium atoms contained in lithium phosphate to the number of moles of iron atoms contained in the mixture was 1.03, and the ratio of the number of moles of ammonium dihydrogen phosphate to the number of moles of iron atoms contained in the mixture was 1.70 mol%. Also, the ratio of the mass of dextrin to the mass of iron atoms contained in the mixture was 18% by mass, and the ratio of the mass of citric acid was 5.0% by mass.
[0077] Granulation step The mixture after the pulverization process was spray-dried to obtain a precursor with an average particle size of 11 to 12 μm. The particle size of the primary particles constituting the precursor was several tens of nm when observed with a scanning electron microscope (SEM).
[0078] Heat Treatment Process 80 g of the obtained precursor was packed into an aluminum crucible measuring 120 mm in length and width and 50 mm in height, and heat-treated at 650° C. for 9 hours in a nitrogen gas atmosphere to obtain a heat-treated product, the positive electrode active material of Example 1. In the heat treatment, nitrogen gas was flowed horizontally near the upper side of the crucible at a flow rate of 40 L / min.
[0079] The obtained positive electrode active material was subjected to phase identification using an X-ray diffractometer. As a result of analysis using CuKα radiation (wavelength: λ=1.54 nm) as X-rays, it was confirmed that the composition was an olivine-type lithium transition metal compound represented by LiFePO4. Similarly, in the positive electrode active materials of the following examples and comparative examples, it was confirmed that the composition was an olivine-type lithium transition metal compound represented by LiFePO4.
[0080] Example 2 A positive electrode active material of Example 2 was prepared in the same manner as in Example 1, except that in the preparation step, the amount of orthoboric acid (H3BO3) added was changed to 1.46 g.
[0081] Example 3 A positive electrode active material of Example 3 was prepared in the same manner as in Example 1, except that in the preparation step, the amount of orthoboric acid (H3BO3) added was changed to 2.17 g.
[0082] Comparative Example 1 A positive electrode active material of Comparative Example 1 was prepared in the same manner as in Example 1, except that orthoboric acid (H3BO3) was not added in the preparation step.
[0083] Comparative Example 2 A positive electrode active material of Comparative Example 2 was prepared in the same manner as in Example 1, except that in the preparation step, 1.16 g of boron phosphate (BPO4) was added instead of orthoboric acid (H3BO3).
[0084] Comparative Example 3 A positive electrode active material of Comparative Example 3 was prepared in the same manner as in Comparative Example 2, except that in the preparation step, the amount of boron phosphate (BPO4) added was changed to 2.32 g.
[0085] Comparative Example 4 A positive electrode active material of Comparative Example 4 was prepared in the same manner as in Comparative Example 2, except that in the preparation step, the amount of boron phosphate (BPO4) added was changed to 3.48 g.
[0086] Comparative Example 5 A positive electrode active material of Comparative Example 5 was prepared in the same manner as in Example 1, except that in the preparation step, the amount of orthoboric acid (H3BO3) added was changed to 4.33 g.
[0087] Comparative Example 6 A precursor was obtained by carrying out the preparation step and the granulation step in the same manner as in Example 1, except that orthoboric acid (H3BO3) was not added in the preparation step. 80 g of the obtained precursor was filled into an aluminum crucible having a length and width of 120 mm and a height of 50 mm, and heat-treated at 650°C for 9 hours in a nitrogen gas atmosphere to obtain a heat-treated product. 0.36 g of orthoboric acid (H3BO3) was added to 60 g of the obtained heat-treated product for a second time, mixed, and then heat-treated at 650°C for 3 hours in a nitrogen gas atmosphere to produce a positive electrode active material of Comparative Example 6. In the heat treatment, nitrogen gas was flowed horizontally near the upper side of the crucible at a flow rate of 40 L / min.
[0088] Comparative Example 7 45.0 g of iron phosphate (Fe3(PO4)2) slurry with an iron atom concentration of 39.2 mass%, 12.69 g of lithium phosphate (Li3PO4), 0.36 g of ammonium dihydrogen phosphate, and 4.59 g of dextrin were placed in a ball mill container and mixed while being ground for 4 hours to obtain a mixture.
[0089] The ratio of the number of moles of lithium atoms contained in the lithium phosphate to the number of moles of iron atoms contained in the mixture was 1.03, the ratio of the number of moles of ammonium dihydrogen phosphate to the number of moles of iron atoms contained in the mixture was 1.00 mol%, and the ratio of the mass of dextrin to the mass of iron atoms contained in the mixture was 26 mass%.
[0090] 80 g of the mixture after the pulverization treatment was filled into an aluminum crucible having a length of 120 mm, width of 120 mm, and height of 50 mm, and heat-treated at 650° C. for 9 hours in a nitrogen gas atmosphere to obtain a positive electrode active material of Comparative Example 7. In the heat treatment, nitrogen gas was flowed horizontally near the upper side of the crucible at a flow rate of 40 L / min.
[0091] Physical property evaluation The positive electrode active material containing the olivine-type lithium transition metal compound obtained above was subjected to the following measurements. The results are shown in Table 1.
[0092] Average particle size The volume-based cumulative particle size distribution of the positive electrode active material obtained above was measured using a laser diffraction particle size distribution measurement device (SALD-3100, manufactured by Shimadzu Corporation), and the volume average particle size D was determined as the particle size corresponding to the cumulative 50% from the small diameter side. 50 asked for.
[0093] specific surface area The BET specific surface area of the positive electrode active material obtained above was measured by a BET specific surface area measuring device (Macsorb, manufactured by Mountec Co., Ltd.) by a gas adsorption method (one-point method) using nitrogen gas.
[0094] Crystalline The X-ray diffraction spectrum (tube current 200 mA, tube voltage 45 kV) of the positive electrode active material obtained above was measured using CuKα radiation, and the diffraction peak obtained near 2θ=32 degrees was fitted by the least squares method using a PseudoVoigt function to calculate the values of θ and β. The crystallinity D was calculated using the following formula (2) from the diffraction peak due to the space group Pnmb(031) plane obtained by the X-ray diffraction method. D = K'λ / (βcosθ) (2)
[0095] In the above formula (3), D represents the crystallinity (Å), λ represents the wavelength of the X-ray source (1.54 Å in the case of CuKα), β represents the integral width (radian), and θ represents the diffraction angle (degree). K' was measured using sintered silicon for optical system adjustment (manufactured by Rigaku Denki Co., Ltd.), and the value at which the crystallinity D due to the (022) plane was 1000 Å when using the above formula (3) was used.
[0096] Oil absorption amount The positive electrode active material obtained above was measured for oil absorption (g / cm) in N-methylpyrrolidone (NMP) in accordance with the method specified in JIS K5101-13-1. 3 Specifically, NMP was added dropwise while mixing the positive electrode active material, and the amount of NMP required to form a slurry was measured, thereby determining the oil absorption amount relative to NMP.
[0097] Carbon content The carbon content (mass %) of the positive electrode active material obtained above was measured using a total organic carbon meter (TOC meter; ON-LINE TOC-VCSH manufactured by Shimadzu Corporation).
[0098] Boron Content The boron content (ppm) of the positive electrode active material obtained above was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES).
[0099] Paste Viscosity In a 150cc container, 6.00g of the positive electrode active material obtained above, 5.56g of carbon paste obtained by mixing a carbon conductive additive (Cabot Litx200) and polyvinylidene fluoride (PVDF; Kureha Corporation, confirmation required) in a mass ratio of 1:1, were added and kneaded with a Mazerustar for 5 minutes. Then, 3.10g of NMP was added and mixed with a Mazerustar for 10 minutes to prepare a measurement paste with a solid concentration of 45.5%. Half of the measurement paste was placed on the base of an E-type viscometer (HAAKE Viscotester iQ) and the viscosity was measured at a temperature of 25°C. The measurement was performed twice, and the arithmetic average value of the two measured values was taken as the paste viscosity (mPa·s). Table 1 also shows the relative viscosity (%) with the paste viscosity of Comparative Example 1 as the reference (100%).
[0100] [Table 1]
[0101] The positive electrode active materials of Examples 1 to 3, which used orthoboric acid (H3BO3) as the boron source, had a specific surface area of 19 m 2 On the other hand, the positive electrode active materials of Comparative Examples 2 to 4, which used boron phosphate (BPO4) as the boron source, maintained a high specific surface area of 13 m 2 The specific surface area remained low at about 1 / g. The positive electrode active material of Comparative Example 5, in which a large amount of orthoboric acid (H3BO3) was added, and the positive electrode active material of Comparative Example 6, in which orthoboric acid was added secondarily, also had low values. The positive electrode active material of Comparative Example 7, in which no boron source was added and no granulation step was performed, also had a low value.
[0102] For the positive electrode active materials of Examples 1 to 3, which used orthoboric acid (H3BO3) as the boron source, the paste viscosity was reduced by about 30% compared to the positive electrode active material of Comparative Example 1, which did not contain a boron source. On the other hand, for the positive electrode active materials of Comparative Examples 2 to 4, which used boron phosphate (BPO4) as the boron source, the paste viscosity tended to increase.
[0103] discharge capacity Using the positive electrode active material obtained above, a battery for evaluation was produced in the following manner, and the discharge capacity was evaluated.
[0104] Preparation of the positive electrode A positive electrode mixture slurry was prepared by dispersing 87.5 parts by mass of the positive electrode active material, 2.5 parts by mass of acetylene black, and 10 parts by mass of polyvinylidene fluoride (PVDF) in N-methyl-2-pyrrolidone (NMP). The obtained positive electrode mixture slurry was applied to an aluminum foil as a current collector, dried, and then compression molded with a roll press machine and cut to a predetermined size to prepare a positive electrode.
[0105] Preparation of the negative electrode A negative electrode slurry was prepared by dispersing and dissolving 97.5 parts by mass of artificial graphite, 1.5 parts by mass of carboxymethyl cellulose (CMC), and 1.0 part by mass of SBR (styrene butadiene rubber) in pure water. The obtained negative electrode slurry was applied to a current collector made of copper foil, dried, compressed and molded with a roll press, and cut to a specified size to prepare a negative electrode.
[0106] Assembling the evaluation battery After attaching lead electrodes to the current collectors of the positive and negative electrodes, a separator was placed between the positive and negative electrodes, and they were stored in a bag-shaped laminate pack. Next, this was vacuum dried at 65°C to remove moisture adsorbed on each member. After that, an electrolyte was injected into the laminate pack under an argon atmosphere and sealed to prepare an evaluation battery. The electrolyte was a mixture of ethylene carbonate (EC) and methyl ethyl carbonate (MEC) in a volume ratio of 3:7, and lithium hexafluorophosphate (LiPF6) was dissolved in the mixture to a concentration of 1 mol / L. The evaluation battery thus obtained was placed in a thermostatic chamber at 25°C, aged with a weak current, and then evaluated as follows.
[0107] discharge capacity The prepared evaluation battery was used for constant-voltage / constant-current charging (cutoff current: 0.005 C) at a charging voltage of 3.65 V and a charging current of 0.2 C, followed by constant-current discharging at a discharge end voltage of 2.0 V and a discharge current of 5 C. The discharge capacity (mAh / g) was measured, and the 5C capacity density was calculated using the measured pellet density value.
[0108] Charge / discharge capacity Using the prepared evaluation battery, low-voltage constant-current charging (cutoff current 0.2mA) was performed at a charging voltage of 3.65V and a charging current of 0.2C, followed by discharging at a discharge end voltage of 2.0V and a charging current of 0.2C, and measuring the charge capacity 0.2C and the discharge capacity 0.2C. Thereafter, low-voltage constant-current charging (cutoff current 0.2mA) was performed at a charging voltage of 3.65V and a charging current of 0.2C, followed by constant-current discharging at a discharge end voltage of 2.0V and a discharge current of 5C, and measuring the discharge capacity 5C. The rate characteristics were calculated from the ratio of the discharge capacity 0.2C to the discharge capacity 5C. The results are shown in Table 2.
[0109] [Table 2]
[0110] The positive electrode active materials of Examples 1 to 3 exhibited rate characteristics equivalent to that of the positive electrode active material of Comparative Example 1, but the positive electrode active materials of Comparative Examples 2 to 7 exhibited decreased rate characteristics. This is believed to be due to the decrease in the specific surface area.
Claims
1. providing a mixture comprising a lithium source, a phosphate source, an iron source, a carbon source, a boron source comprising an oxoacid of boron, and a liquid medium; granulating the mixture to obtain a precursor; and heat treating the precursor to obtain a lithium transition metal compound having an olivine structure. the mixture has a total molar amount of boron atoms contained in the boron source that is greater than 0 mol % and less than 3 mol % with respect to a total molar amount of iron atoms contained in the iron source.
2. The mixture is prepared by grinding a premix containing a lithium source, a phosphate source, an iron source, and a liquid medium, and then mixing the premix with a carbon source and a boron source; A premix containing a lithium source, a phosphate source, an iron source, a carbon source, and a liquid medium is ground, and then a boron source is added to the premix. A premix containing a lithium source, a phosphate source, an iron source, a boron source and a liquid medium is milled, and then a carbon source is mixed therein; or The method for producing a positive electrode active material for a secondary battery according to claim 1, wherein the positive electrode active material is prepared by pulverizing a preliminary mixture containing a lithium source, a phosphate source, an iron source, a carbon source, a boron source and a liquid medium.
3. The method for producing a positive electrode active material for a secondary battery according to claim 2 , wherein the pulverization treatment is carried out for 10 hours or more using a ball mill.
4. 2 . The method for producing a positive electrode active material for a secondary battery according to claim 1 , wherein the mixture has a mass ratio of the carbon source to iron atoms of 15 mass % or more and 30 mass % or less.
5. The precursor has a volume average particle size D 50 2. The method for producing a positive electrode active material for a secondary battery according to claim 1, wherein the average particle size is 1 μm or more and 20 μm or less.
6. The method for producing a positive electrode active material for a secondary battery according to claim 1 , wherein the heat treatment is carried out in a nitrogen atmosphere at a temperature of 500° C. or more and 700° C. or less.
7. The lithium transition metal compound has an olivine structure, the boron content in the composition is greater than 0 ppm and less than 1900 ppm, and the specific surface area is 15 m 2 / g or more.
8. 8. The positive electrode active material for secondary batteries according to claim 7, which has an oil absorption of 30 ml / 100 g or less in N-methyl-2-pyrrolidone.
9. When pelletized at a pressure of 3.5 MPa, the pellet density was 2.00 g / cm 3 The positive electrode active material for a secondary battery according to claim 7 .
10. The positive electrode active material for a secondary battery according to claim 7 , wherein the lithium transition metal compound has a composition represented by the following formula: Li x (Fe (1-y) M 1 y ) (1-z) M 2 z (2O 4 ) w (In the formula, x, y, z, and w satisfy 0.9<x<1.3, 0≦y<1, 0≦z<0.3, and 0.9≦w≦1.
3. M 1 contains at least one metal element selected from the group consisting of Mn, Co and Ni, 2 contains at least one metal element selected from the group consisting of Mo, Mg, Zr, Ti, Al, Ce and Cr)
Citation Information
Patent Citations
Boron-substituted lithium-inserted compounds, electrode active materials, batteries and electrochromic devices
JP2007502249A